THE ROLE OF APQP (ADVANCE PRODUCT QUALITY PLANNING) IN THE FINAL PRODUCT - Schineider, Oriel Alan; Gasparotto, Angelita Moutin Segoria (Revista Interface Tecnológica, 2020)
This article reflects on the method APQP (Advanced Product Quality Planning) in order to explore how it is applied by automotive companies, describing its definition, how it can be used and its stages for application. It is a method that guides and makes it possible to verify the steps in the process of developing or changing a product. This process involves several departments of the company, allowing the product to satisfy the customer, aiming at quality and cost reduction from the planning phase to the launch of the item, evaluating possible failures in the process. The present research is considered bibliographic and descriptive and to exemplify the use of the APQP, two case studies from a scientific article have been described that demonstrate in practice how automobile organizations apply this resource. From this perspective, APQP is seen as a very useful tool that helps companies achieve their organizational goals and also assists for continuous improvement in their quality processes.
Keywords: APQP; Quality; Product Development Steps; Customer Satisfaction